RANCANG BANGUN HULU HILIR, PEMODELAN DAN KEBIJAKAN PEMERINTAH PADA AGRIBISNIS KEDELAI - Soetriono Soetriono (Jurnal Sosial Ekonomi Pertanian (J-SEP), 2010)
Soybean commodity plays an important role in economy since most of the commodities (95%) are used for agro-industry and 96% of them is raw materials for tofu and tempe agro-industry. Domestic production has not been able to fulfill internal need of it, where 55% is still fulfilled by import. This research is intended to identify the competitiveness of on farm agribusiness of soybean by institutional input and policy simulation; the relation between upstream and downstream system activities of soybean agribusiness; model and strategy to eliminating soybean farmers’ powerlessnessThe research area was determined purposively in East Jawa Jember considering that Paleran Village was a village that had Prime Farm program and Curah Lele village was the centre village of soybean marked with Prime Farm program. Samples were taken by applying by simple random sampling.Analysis method by using competitive and comparative advantages (competitiveness) applied Policy Analysis Matrix (PAM), policy scenario, modeling and strategy to eliminating soybean farmers’ powerlessness by Force Field Analysis (FFA); the research results showed:1. Private profitability and social profitability of on-farm agribusiness of soybean in research area had efficiency and comparative and competitive advantages, meaning that on-farm agribusiness of soybean had competitiveness.2. Government policy toward output tradable provided negative effect on on-farm agribusiness of soybean indicated by NPCO value lower than one. Government policy toward input tradable gave positive effect on on-farm agribusiness of soybean performed by NPCI value lower than one. Collectively, government policy on input output tradable and input non tradable affected negatively on on-farm agribusiness of soybean shown by negative NPT and SRP values and PC value lower than one.3. The change of government policy toward import tariff of soybean and exchange rate of rupiah still remained giving positive effects on efficiency and competitiveness of soybean on-farm agribusiness, while the change of government policy on output tradable affected negatively on on-farm agribusiness of soybean. The change of government policy on input tradable still provided positive effects on on-farm agribusiness of soybean. The change of government in input output tradable and input non tradable remained negative, while the effect of the change of government policy on input and output tradable gave positive effects together on on-farm agribusiness.4. On-farm agribusiness of soybean under Prime Farm Program had stronger competitiveness compared to non-prime farm program though held in central area..5. In order to overcome powerlessness of soybean farmers, some efforts on the basis of FFA analysis from upstream to downstream sub-systems are necessarily undertaken, they are:a. Sub-system of up-stream agribusiness; (1) to intensify extension on the field of knowledge and technology; (2) the best quality seeds development and (3) improvement on distribution channel of production tools.b. Sub-system of on-farm agribusiness; organic fertilizer development and intensive supervision by related departments (Agriculture Department), especially on pest and disease control. c. Sub-system of down-stream agribusiness; it is necessary to establish farmer’s association, soybean industry and to develop modern processing technology such as ketchup and soybean milk.d. Sub-system of marketing is needed to organize market that is related to major agribusiness market.e. Sub-system of supporting services; it is important to develop market at village level, to establish agribusiness and to optimize extension personnel that all become strong requirements.Kata kunci: soybean agribusiness, policy